2016
DOI: 10.1002/admi.201600373
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Formation of Zinc Oxide Micro‐ and Nanostructures via DUV Direct Patterning

Abstract: Various kinds of zinc oxide (ZnO) nanostructures, such as ZnO nanowires, ZnO nanobelts, ZnO nanosheets, and ZnO nanorods are promising building blocks for nanoscale systems. However, to precisely control the size, shape, and to make a controlled assembly of synthesized ZnO nanostructures are major diffi culties in the development of bottom-up devices. To overcome the challenge regarding reproducibility and positioning, a new method is proposed, deep ultra-violet (DUV) direct photo-patterning, to create ZnO mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…For the MO part, after thermal annealing, structural variation may occur due to the removal of embedded organic compounds. The volume reduction, in some cases, is more than 85%, which dramatically reduces the size of the patterned structures . Some studies observed the appearance of a double‐peak profile on the material topography after annealing, and this change may increase the surface roughness for the subsequently deposited layers .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the MO part, after thermal annealing, structural variation may occur due to the removal of embedded organic compounds. The volume reduction, in some cases, is more than 85%, which dramatically reduces the size of the patterned structures . Some studies observed the appearance of a double‐peak profile on the material topography after annealing, and this change may increase the surface roughness for the subsequently deposited layers .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other SDP techniques, photopatterning has the advantage of making nanoscale MO patterns for small‐dimension devices by using DUV or EUV lithography and is more efficient and cost‐effective than e‐beam writing. Yeh et al used DUV interference for direct patterning of the photosensitive zinc methacrylate (ZnMAA) precursor into nanoscale periodic lines with a 300 nm line width, as shown in Figure a . After thermal annealing, ZnMAA patterns could be converted into ZnO patterns, as shown in Figure b.…”
Section: Electronic Applications Of Solution Direct‐patterned Mo Micrmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, zinc methacrylate was used to prepare ZnMAA resist with photosensitivity to DUV light of 193 nm . In the present study, conditions to introduce cobalt (II) acetate into ZnMAA solution with an atomic ratio Co/(Co + Zn) = 0.15 were defined and a stable photosensitive Co‐doped ZnMAA precursor solution could be successfully prepared.…”
mentioning
confidence: 95%